Effects of Heating Rate on the Dynamic Tensile Mechanical Properties of Coal Sandstone during Thermal Treatment. (18th October 2017) - Li, Ming; Mao, Xianbiao; Pu, Hai; Chen, Yanlong; Wu, Yu; Zhang, Lianying
Abstract : The effects of coal layered combustion and the heat injection rate on adjacent rock were examined in the process of underground coal gasification and coal-bed methane mining. Dynamic Brazilian disk tests were conducted on coal sandstone at 800°C and slow cooling from different heating rates by means of a Split Hopkinson Pressure Bar (SHPB) test system. It was discovered that thermal conditions had significant effects on the physical and mechanical properties of the sandstone including longitudinal wave velocity, density, and dynamic linear tensile strength; as the heating rates increased, the thermal expansion of the sandstone was enhanced and the damage degree increased. Compared with sandstone at ambient temperature, the fracture process of heat-treated sandstone was more complicated. After thermal treatment, the specimen had a large crack in the center and cracks on both sides caused by loading; the original cracks grew and mineral particle cracks, internal pore geometry, and other defects gradually appeared. With increasing heating rates, the microscopic fracture mode transformed from ductile fracture to subbrittle fracture. It was concluded that changes in the macroscopic mechanical properties of the sandstone were result from changes in the composition and microstructure.